TOWARD, a metabolic health intervention, demonstrates robust 1-year weight loss and cost-savings through deprescription - Buchanan, Laura; Calkins, Matthew; Kalayjian, Tro; Norwitz, Nicholas G.; Teicholz, Nina; Unwin, David; Soto-Mota, Adrian (Frontiers in Nutrition, 2025)
BackgroundCost, scalability, and durability represent major challenges to the implementation of intensive lifestyle treatments for obesity and diabetes. We previously reported pilot data from a 6-month intervention in which a self-insured manufacturing company partnered with a metabolic health clinic that utilizes therapeutic carbohydrate reduction (TCR), asynchronous monitoring, and a community-based approach to treat employees with metabolic disease. This manuscript presents weight loss and cost-savings from deprescription at the 12-month time point.Methods50 employees, mean BMI 43.2 ± 8.7 kg/m2, 64% with prediabetes or type 2 diabetes, were enrolled in the multimodal TOWARD telemedicine intervention, which includes: Text-based communications, Online interactions, Wellness coaching, Asynchronous education, Real-time biofeedback and remote monitoring, and Dietary modifications that emphasizes TCR.Results41 completed the one-year intervention. Mean weight loss for the 50 subjects in the intention-to-treat analysis was 19.5 ± 11.4 kg, corresponding to 15.5% total body weight loss with concomitant deprescription of 96 medications, while starting only 8 medications. In patients who discontinued GLP-1 receptor agonists, weight loss continued or was maintained. Annualized cost savings from the TOWARD approach were approximately -$1700 per patient, as compared to an annualized cost burden of roughly +$13000 per patient for a GLP-1 receptor agonist.ConclusionThe TOWARD approach represents a scalable metabolic health intervention that demonstrates robust improvements in weight while simultaneously allowing for deprescription leading to substantial cost savings. TOWARD could serve as a scalable tool to facilitate intensive lifestyle intervention with efficacy on par with GLP-1 receptor agonists.